2016
DOI: 10.15376/biores.11.3.6452-6463
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fiber Treatment on the Oil Absorption Characteristics of Plant Fibers

Abstract: Most plant fibers are good sorbents of oil; however, synthetic sorbents have a much higher sorption capacity (SC) than plant fibers. This study evaluated the effect of fiber treatments, specifically hot-water treatment and mercerization, on the absorption characteristics of selected plant fibers. Five common plant fibers-corn residues, soybean residues, cotton burr and stem (CBS), cattail, and oak-were evaluated for their absorption characteristics in crude oil, motor oil, deionized (DO) water, and a 80:20 mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 19 publications
3
29
0
1
Order By: Relevance
“…The sorptive capacity defined for oil-burning products is 450–500% m/m (Wong et al 2016). In individual studies, broadleaf cattail seeds mercerised with NaOH (N, Na) have shown a sorptive capacity of 300–770%, which was the lowest value; the highest value was noted for the W and G seeds (2495–2661%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sorptive capacity defined for oil-burning products is 450–500% m/m (Wong et al 2016). In individual studies, broadleaf cattail seeds mercerised with NaOH (N, Na) have shown a sorptive capacity of 300–770%, which was the lowest value; the highest value was noted for the W and G seeds (2495–2661%).…”
Section: Resultsmentioning
confidence: 99%
“…Their sorptivity is quite considerable and often exceeds 100 g of an oil-related product in proportion to 1 g of sorbent (1000%). Furthermore, they can be neutralised in combustion plants for dangerous wastes, thus providing the opportunity to regain energy (Wong et al 2016). Still, other authors pay attention to another option—desorption.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was observed that though alkaline treatment sample gave the highest adsorption capacity than hot water treated sample, the reverse was observed with the percentage of oil removed. This may be caused by higher weight gain from the adsorption of water molecules rather than crude oil after the adsorption process [19]. Similarly, the rise in percentage of oil removed observed in hot water treated sample can be attributed to its increase in floating ability.…”
Section: Effects Of Adsorbent Dosage On the Adsorption Of Crude Oilmentioning
confidence: 96%
“…ported as compared with silk-floss, sisal, sawdust and coir fiber [20]. A projection is thus inferred that by modifying the fibre structure through pretreatment, this will lead to modification in the fiber surface structure as well as to alteration in the surface energy, and possibly, an improvement in the adsorption ability for crude oil would be obtained [16] [19].…”
mentioning
confidence: 99%
“…Because of this property, 1 g of unmodified sorbent absorbed high amount of water -14.54 g. Mercerization of the sorbent decreased water absorption by almost 7%. Researchers have treated cellulose fibers with alkali in different concentrations and even at low NaOH concentrations fibres can fibrillate, resulting in a reduced fibre diameter which causes a decrease of the surface area (Wong, McGowan, Bajwa, & Bajwa, 2016). The effect of alkali on the cellulose component of fiber causes swelling; therefore, the natural crystalline structure of the cellulose I relaxes.…”
Section: Water Sorption Capacity Testmentioning
confidence: 99%